KADAR VITAMIN C PADA KOMBUCHA BUNGA TELANG (Clitoria ternatea) PASKA FERMENTASI DAN MASA SIMPAN 7 HARI - Vanya Alyssa Huda; Lailatus Sa’diyah (Bioscientiae, 2024)
Telang Kombucha is a fermented drink made from telang flower fermented by SCOBY in 7 days. Aftrer fermenting telang Kombucha in 7 days, kombucha then stored for 7 days more to observed the vitamin C. The aim of this research is to determine and compare the vitamin C level of Telang (Clitoria ternatea) kombucha after 7 days stored. Measurements of vitamin C levels were performed using UV- Vis spectrophotometry and calculated using linear regression equations. The maximum wavelength of ascorbic acid obtained were 262 with 0,519 absorbance. After telang kombucha stored for 7 days vitamin C levels obtained raised from 84,1% (fermented 7 days) to 90,7% (stored 7 days after fermentation). In this study, it can be concluded that there is an increase in vitamin C levels in telang kombucha after storing 7 days and it has higher vitamin C than kombucha without telang. So, it is necessary to drink telang kombucha rather than kombucha tea to increase healthy immune system.